Morphological and Morphometrical Characterization of Scapula Bone of Fishing Cat, Leopard Cat and Small Indian Civet - Pathak, Satish K. (Indian Journal of Veterinary Anatomy, 2020)
Scapula was half moon shaped in fishing cat and triangular in civet. In leopard cat spine was not as inclined towards infraspinous fossa as in fishing cat and civet. Leopard cat glenoid cavity was oval like fishing cat. Tuber scapulae was more raised in civet than fishing cat. acromion process was slightly inclined towardsanterior border In fishing cat and civet whereas straight in leopard cat. Scapular index was highest in fishing cat and lowest in leopard cat. Diameter of glenoid cavity was highest in small Indian civet and lowest in leopard cat.